Green jobs in green transformation story - Alkan, B. (IGI Global, 2024)
Governments around the world are enacting green recovery and transition programs in collaboration with international agencies. Their coordinated efforts attempt to balance economic growth with environmental preservation, emphasizing that for a sustainable and green future the green transformation is an urgent requirement. The employment component of the green transformation has significant social and economic repercussions. Depending on how prepared countries are for the transition process, skill adaptation and the creation of new job opportunities can provide socioeconomic benefits. "Green jobs" are discussed in the chapter as an important part of the transition strategy to a green economy. The chapter outlines what a "green job" is and is not, presents the connection between employment and skills, and emphasizes the relevance of green jobs in the transition process. © 2024, IGI Global. All rights reserved.
Keywords: [No Keyword Available]